Recent Progress in Nanoscale Covalent Organic Frameworks for Cancer Diagnosis and Therapy - Yao, Shuncheng; Liu, Zhirong; Li, Linlin (Nano-Micro Letters, 2021)
Covalent organic frameworks (COFs) as a type of porous and crystalline covalent organic polymer are built up from covalently linked and periodically arranged organic molecules. Their precise assembly, well-defined coordination network, and tunable porosity endow COFs with diverse characteristics such as low density, high crystallinity, porous structure, and large specific-surface area, as well as versatile functions and active sites that can be tuned at molecular and atomic level. These unique properties make them excellent candidate materials for biomedical applications, such as drug delivery, diagnostic imaging, and disease therapy. To realize these functions, the components, dimensions, and guest molecule loading into COFs have a great influence on their performance in various applications. In this review, we first introduce the influence of dimensions, building blocks, and synthetic conditions on the chemical stability, pore structure, and chemical interaction with guest molecules of COFs. Next, the applications of COFs in cancer diagnosis and therapy are summarized. Finally, some challenges for COFs in cancer therapy are noted and the problems to be solved in the future are proposed. Highlights: 1 Recent progress in nanoscale covalent organic frameworks (COFs)-mediated nanomedicines for cancer diagnosis and therapy is comprehensively summarized in this review. 2 Future perspectives and challenges regarding COFs-mediated nanomedicines for diagnosis and therapy are discussed, with particular emphasis on possible clinical translation.